The impact of the project learning strategy on the achievement of the students of the Department of Art Education in Interior Design (Journal of the College of Basic Education, 2022)
This study aimed to know the effect of the project's learning strategy on the achievement of students of the Department of Art Education in the subject of interior design. In order to achieve the goal of the research, the researcher used the experimental method on a sample of students from stage third from the Art Education Department, and the research sample consisted of (60) students who were divided into the experimental and control groups equally. The researcher used a cognitive achievement test (pre and post) and a skill test. In order to reach the results of the research, the researcher used a set of (statistical methods, including: the t-test for two independent samples, and this test was used for equivalence in the research variables (chronological age - gender - previous experience) between the members of the experimental and control groups. Paragraph difficulty equation: This equation was used to identify the degree of difficulty of the achievement test paragraphs Paragraph discrimination equation This equation was used to find discrimination for the achievement test paragraphs Effectiveness of alternatives: It was used to calculate the effectiveness of incorrect (wrong) alternatives for the achievement test paragraphs Cooper's equation was adopted to calculate the percentage of agreement between the referees, and Keodor Richardson equation / 20 was adopted to calculate the stability coefficient of the items of the cognitive test. The most important results of the search showed:The experimental group that studied the interior design subject according to the project’s learning strategy outperformed the control group that studied in the usual way with the cognitive and skill test. Based on the results of the study, the researcher recommended several recommendations, including:1- Applying the project’s learning strategy in teaching students of other relevant educational institutions (faculties of fine arts and institutes of fine arts) after it has proven to be more effective in education than the usual method, with the aim of helping them fulfill the requirements of the subject of interior design.To complement the current research, the researcher suggested a number of proposals, including:1- The impact of the project’s learning strategy on developing the skills of students of the Institute of Fine Arts in sculpture.